Anxiety Of Alexandra Maria Ellena Delgado In StuartGillard's The Cutting Edge: A Psychoanalytic Approach - Septiana, Vitalityas, Drs. Abdillah Nugroho, M.Hum, Siti Fatimah, S. Pd, M. Hum (2013)
The major problem of this study is how anxiety reflected in the major character's personality. The aim of this study is to analyze Stuart Gillard's The Cutting Edge the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on major character, namely Alexandra Maria Ellena Delgado. The benefit of this research is to give addition all information to be used by other literature researchers who are interested in analyzing this movie. This study uses two data source, namely primary and secondary data source. The primary data source is the play script itself, while the secondary data are taken from some information needed.The method of data collection is qualitative method. Based on the analysis, the study of this research comes from the major character problem. It purposes to analyze the movie using individual psychologycal perspective. The steps to conduct this research are (1) determining the type of the study, (2) determining the object of the study, (3) determining the data and data sources, (4) determining the technique of data collection, and (5) determining technique of data analysis. The result of the study found that there is a relationship between The Cuttingedge movie and psychoanalytic approach, first on the structural element of the movie; where the message to The Cuttingedge movie shows that Alexandra Maria Ellena Delgado as the major character that she want to be a beautiful ice skater. The point of view is, the director wants to show the struggle of life of Delgado's. The theme of the movie is the basic idea of story in which the author portrays through conflicts of characters with other character or with life events. The anxiety of Alexandra related with psychoanalytic approach is that the doubt, fear, and worried of Alexandra makes her brave to take the second chance, and make her dream comes true namely to be a beautiful ice skater.